Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) Untuk Meningkatkan Hasil Belajar Matematika Siswa - Pramasanti, Desak Ketut (Jayapangus Press, 2024)
This research aims to determine whether the application of the Think-Pair-Share (TPS) cooperative learning model can enhance students' mathematics learning outcomes. The Classroom Action Research (PTK) was conducted in class VII D of SMP Negeri 6 Kintamani. The subjects comprised all students in class VII D of SMP Negeri 6 Kintamani during the first semester of the 2022/2023 academic year, totaling 32 individuals, with 17 males and 15 females. The research focused on students' mathematics learning outcomes. This study on learning enhancement occurred over two cycles: cycle I covered integers, and cycle II involved fractions. Mathematics learning outcomes were assessed based on the scores obtained by students in learning outcome tests. Data collection utilized observation and test methods. Quantitative descriptive analysis and qualitative descriptive analysis were employed for data analysis. Student mathematics learning outcomes data were processed using averages and classical completeness. The success criterion for this classroom action research was defined as average student mathematics learning results falling within the 'good' category (77-86) with a minimum classical completeness of 85%. Analysis of the research revealed an increase in average student mathematics learning outcomes, rising from 71.76 (categorized as fairly good) in cycle I to 80.00 (categorized as good) in cycle II, marking an increase of 8.24. Additionally, there was an increase in learning completeness from 61.76% in cycle I to 88.24% in cycle II, marking a rise of 26.48%. The conclusion drawn from this research is that the application of the Think-Pair-Share (TPS) cooperative learning model positively impacts students' mathematics learning outcomes.